Budget Planning And The Quality Of Educational Services In Uganda Public Universities: A Case Study Of Kyambogo University - Basheka, Benon C.; Nabwire, Addah (Educational Research and Reviews, 2013)
This paper examines the relationship between budget planning and the quality of educational services at Kyambogo University in Uganda. We argue that the manner in which the university’s budget planning activities are conducted determines in a significant way (by 76.8%) the quality of the services offered by public universities in Uganda. The findings are original and contribute to the body of education quality in developing countries. The results are compared with both local and international findings to suggest policy and managerial implications.
Keywords: Budget management, Kyambogo University, Uganda.